Risk Analysis of Firm Energy Coverage in Colombia in the Medium Term - Moreno, Ricardo; Cantillo, Sergio A.; Carrillo-Rodriguez, Lilian A. (International Journal of Energy Economics and Policy, 2021)
The recent auction of firm energy and the decisions on medium-term coverage give rise to risks in the supply of electricity in Colombia in the coming periods. Taking into account the possible risks that may arise, such as: non-compliance with FEO due to generation units (six (6) non-compliances during 2015-2016 term), the delay of generation projects with committed firm energy (Hidroituango case) and the availability of firm energy in the market, imply a systemic risk for the electric power supply in the medium term. Through the study of technical documents and resolutions, issued by the CREG, about the medium term energy balances in 2018, firm energy supply and demand balances were reconstructed, including the results of the last FEO auction carried out in the first quarter of 2019, in order to carry out a risk analysis based on these same scenarios. It was observed that the amount of FEO auctioned exceeds the quantity of demand projected, meaning that the CREG assumed a conservative position by purchasing more energy than necessary (8650 GWh-year and 1027 GWh-year respectively), this is a situation that has occurred on more than one occasion. Keywords: Reliability Charge, Firm Energy, Firm Energy Obligation, Risk JEL Classifications: L78, L94, Q41, Q42, Q48 DOI: https://doi.org/10.32479/ijeep.10490